Feasibility of dental education in patient-free settings: a Delphi study with Latin American experts - Mejía Pérez, Paula Natalia (2026)
Objectives: To explore the perceptions of experts and faculty members, both national and international, working in public and private universities, regarding the challenge of training dentists under quality standards in a potential scenario without direct patient care, as projected in the post-pandemic period. Materials and Methods: The Delphi method, a qualitative approach also known as a consensus technique, was employed to address the research question. Twelve experts from Colombia and other countries were selected through peer academic referral. A structured questionnaire comprising seven core categories was designed and distributed via email. Data were analyzed through processes of condensation and categorization into recurrences, divergences, and trends. Additionally, the Voyant tool was used to complement the content analysis. Results: Key informants expressed a predominantly negative stance toward the possibility of teaching dentistry in the absence of patients. They emphasized the importance of the dentist–patient relationship and direct human contact, considering it an irreplaceable component in the educational process. Conclusions: Experts agree that dental education requires the active participation of patients to achieve meaningful and lasting learning. However, they highlight the need to diversify and innovate teaching methods in alignment with the demands of contemporary contexts.Principio del formulario